MULTIKULTURALISME DALAM NOVEL MENGURAI RINDU KARYA NANG SYAMSUDIN - Jasril; Asmawati (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study aims to describe multiculturalism as reflected in the novel Mengurai Rindu by Nang Syamsudin. Data was collected using observation, reading, and note-taking techniques and analyzed through content analysis methods with heuristic and hermeneutic reading approaches, interpreted using the sociology of literature theory. The findings reveal that Mengurai Rindu by Nang Syamsuddin is a literary work that: (1) highlights the diversity of society—including ethnicity, culture, and religion; (2) contains multicultural elements such as (a) solidarity and brotherhood, (b) gender equality, (c) family values, and (d) sharing and power control; (3) in addition to promoting multicultural values, it also presents anti-multicultural values, such as prejudice and stereotypes against other groups, particularly in interethnic relations; (4) the emergence of anti-multicultural values is influenced by the desire to preserve the purity of lineage; and (5) diversity as a form of multiculturalism can bring happiness and peace if managed well and if mutual respect for differences is maintained.